Aims Increased expression of senescence markers p14ARF and p16INK4a in breast cancer is associated with an increased risk of disease recurrence and poor survival outcome - Rahmawati Pare; Joo, Shik Shin; Cheok, Soon Lee (John Wiley & Sons, Inc., 2016)
Breast cancer is a hormonally driven disease. Cellular senescence is an age‐related irreversible cell cycle arrest at the G1 phase upon induction. The aim of this study was to characterize the expression patterns of the senescence markers p14ARF, p16INK4a and p21WAF1/Cip1 during breast cancer progression in a large patient cohort. Methods and results: We conducted a retrospective study of 1080 patients with invasive ductal carcinoma, no special type, over an 11‐year period. We performed immunohistochemical staining on tissue microarrays that included normal, benign hyperplasia, ductal carcinoma in situand invasive ductal carcinoma tissue from each patient. Invasive ductal carcinomas showed higher expression of p14ARF and p16INK4a but lower expression of p21WAF1/Cip1than non‐malignant tissues. There were significant correlations of normal, benign, preinvasive and malignant tissues with p14ARF, p16INK4a and p21WAF1/Cip1 expression (P < 0.05). Univariate comparison showed a correlation between high p16INK4a expression and poor survival (P = 0.000) and an increased risk of relapse (P = 0.000), whereas high p14ARF expression correlated only with an increased risk of relapse (P = 0.038). Multivariate analysis showed p16INK4a to be an important prognostic factor for overall survival (P = 0.011) and disease‐free survival (P = 0.004), with p14ARF also being a significant prognostic factor for disease‐free survival (P = 0.043). Moreover, patients showing both high p16INK4a expression and and high p14ARF expression had an adjusted three‐fold increased risk of disease recurrence (P < 0.05) and a two‐fold increased risk of all‐cause‐related death (P < 0.05). Conclusions: These finding suggest p16INK4a expression and p14ARF expression may play an important role in the progression of proliferative breast tissue to invasive cancer, and may be useful as prognostic factors